(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Today’s society is becoming more interactive and social, although the style of communication has changed. The exchange of information, unlike the earlier days, takes place through Facebook, Twitter, Emails, YouTube, WhatsApp, and so on, to communicate and disseminate information and knowledge with others. Political deliberation has been conducted through online media where politicians are able to reach out to the citizens virtually, notwithstanding their geographic location, and pursue information exchange and discussion.In recent times new media has contributed to movements such as “Occupy Wall Street” in the United States, the rise of Spain’s “Indignados” or anti-austerity movement, demonstrations in Tehran and Moscow, the rebellion in Egypt which lead to the downfall of President Hosni Mubarak, the “Twitter Revolution” in Moldova, etc. (La Pietra Dialogues, 2012).Closer to home, the 2014 general elections in India were also influenced considerably by the use of new media such as social media. Savvy politicians leveraged social media cleverly to reach out to voters so much so that their rivals were forced to follow suit. The fresh voter population, aged between 18 and 23 years, who are active on the different forms of social media responded to the online “campaigning” and turned out in large numbers to vote, an unprecedented event in the history of Indian elections (Chao, 2014 Ramalingegowda, 2014).This paper proposes to perform a review of the studies associated with the different social media used by politicians in India to woo voters and the response of the voters to this online political discourse.